Auditor's Proficiency North Sumatera: Unveiling Fraud With Skepticism - Zulia Hanum (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
Numerous instances of Fraud frequently arise within various companies, often stemming from lapses in the professional ethics of auditors. This research explores fraudulent activities by examining the impact of auditor experience, capabilities, and professional scepticism. The chosen research focus is Public Accounting Firms in North Sumatra, specifically Medan. Employing descriptive statistical analysis with quantitative data, the research utilises the saturated sampling method with a sample of 199 respondents from a population of 25 Public Accounting Firms. Hypothesis testing results reveal a significant correlation between Auditor Experience, Auditor Capability, and Professional Skepticism in detecting Fraud. The findings also indicate that Professional Skepticism significantly influences Auditor Capability in fraud detection. Moreover, the testing results suggest that the relationship between Auditor Experience and Auditor Capability is mediated by Professional Skepticism as an intervening variable, shedding light on the complex dynamics influencing fraudulent behaviour within the auditing profession.